Reanimating feminist archives: ethics and praxis - Webb, Sharon; Thomson, Rachel; Moore, Niamh (Frontiers in Communication, 2024)
This study explores the complexities of developing feminist archives with a particular focus on the ‘Feminist Approaches to Youth Sexuality (FAYS)’ archive, created as part of the Reanimating Data project (RAD, 2018-21). Through this case study, we explore the ethical considerations and practices involved in reanimating a landmark feminist study, the Women, Risk, and AIDS Project (WRAP), and emphasize the ethical dimensions of reanimation processes, considering feminist ethics of care and risk. We also explore the concept of rematriation, which is rooted in indigenous feminist scholarship. This concept has become a guiding principle in our efforts to return WRAP to its geo-political context. As such, the article is structured into the following three sections: data in the attic, on recovery and rematriation; feminist ethics, on care and risk; and feminist archival praxis, on reanimating and language.